Concomitant wild type transthyretin amyloidosis & severe aortic stenosis in elderly Indian population: pilot study. (14th October 2021) - Singal, A K; Bansal, R; Singh, A; Dorbala, S; Saxena, A; Karthikeyan, G; Ramakrishnan, S; Bisoi, A K; Hote, M P; Rajashekar, P; Chowdhury, U K; Devagourou, V; et al.
Abstract: Background: Prevalence of both severe aortic stenosis (AS) and wild-type transthyretin cardiac amyloidosis (wtTTRCA) increases with age. Dual disease (AS+wtTTRCA) occurs in a significant proportion of patients undergoing aortic valve replacement. Prognostic significance of this dual disease is not established. Purpose: TTRCA distribution has ethnic variability. This has not been studied in an Indian/Asian population before. India alone has >4.6 million estimated elderly individuals with severe AS. This pilot study was designed as part of a larger study to determine the prevalence of coexistence of severe AS and wtTTRCA in elderly Indian population and identify non-invasive predictors of its diagnosis. Methods: Symptomatic severe AS patients aged ≥65 years undergoing surgical aortic valve replacement (SAVR) were enrolled. Detailed 2-D transthoracic echocardiogram including speckle tracking and longitudinal strain assessment was done preoperatively. TTRCA diagnosis was based on preoperative 99m-Technitium pyrophosphate scan (PYP), and intra-operatively obtained basal inter-ventricular septum (IVS) biopsy and excised native aortic valve subjected to histopathological examination (HPE). Congo red staining and immunohistochemistry using TTR monospecific antibodies were performed to identify and sub-type amyloid respectively. Serum/urine protein electrophoresis with serum immunofixation to rule out primary amyloidosis and genetic analysis to rule out mutant TTRCA were also done. Results: SAVR was done in 46 severe AS patients (mean age 70±5 years, 70% men), 32 (70%) of whom also underwent PYP scan. Significant PYP uptake (Perrugini grade II or III) was seen in 3 (9%) patients (Figure 1E, F). On HPE, 33 (72%) native aortic valves had amyloid deposits, of which 19 (58%) had TTR deposition (Figure 1A, B, C, D). However, none of the IVS biopsies showed amyloid deposits. None of the patients had evidence of monoclonal protein elevation and mutation in the TTR gene. Non-invasive markers of this dual coexistence included elevated troponin-I (≥26.2 pg/mL, 35% vs 67%), combined elevated troponin-I & NT-ProBNP (≥26.2 pg/mL & ≥400 pg/mL, 24% vs 33%), and significantly low myocardial contraction fraction (≤30%, 72% vs 100%), deceleration time (207±80 msec vs 85±23 msec) and global longitudinal strain (−19.3±4.3% vs −13.6±3.7%). At median follow-up of 12.5 months, 1 patient each had died in TTR negative and TTR positive groups (3% vs 33%). The results are summarised in the central illustration (Figure 2). Conclusion: In the Indian context, concomitant existence of severe AS and wtTTRCA is common. This pilot study suggests an absolute burden of >450, 000 patients with dual disease of AS and wtTTRCA, in those otherwise believed to have lone severe AS. Further larger studies are thus indicated to establish the prevalence of this dual disease and to assess its prognostic implication. Funding Acknowledgement: Type of funding sources: None.